2019
DOI: 10.3389/fonc.2019.00441
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Different Chemotherapy Regimens for Advanced Biliary Tract Cancer: A Systematic Review and Network Meta-Analysis

Abstract: Background: Although gemcitabine plus cisplatin (GP) is considered as standard chemotherapy for patients with advanced biliary tract cancer (BTC), the optimal regimen remains unknown. Methods: Using Network meta-analysis (NMA), a systematic review was conducted to find the most effective chemotherapy regimen for advanced BTC. We searched PubMed, Web of Science, Embase, Scopus and the Cochrane Library for articles published before October 6, 2018. Articles about chemotherapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 50 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…Meanwhile, we also found that GEMOX+erlotinib was better than the protocol fluorouracil+folic acid in OS, PFS, and ORR. Both previous NMAs also suggested that protocol gemcitabine was superior to protocol fluorouracil ( 38 , 39 ). Cediranib combination chemotherapy in this NMA also has preferable ORR and tolerance.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Meanwhile, we also found that GEMOX+erlotinib was better than the protocol fluorouracil+folic acid in OS, PFS, and ORR. Both previous NMAs also suggested that protocol gemcitabine was superior to protocol fluorouracil ( 38 , 39 ). Cediranib combination chemotherapy in this NMA also has preferable ORR and tolerance.…”
Section: Discussionmentioning
confidence: 93%
“…However, there is still a lack of evidence-based evidence on how doctors should choose many protocols. Li et al ( 39 ) also compared the efficacy of chemotherapy protocols in his recent NMA on advanced BTC but did not compare AEs.…”
Section: Discussionmentioning
confidence: 99%
“…This finding has also been reported in first-line chemotherapy. 13 , 30 During the follow-up, we found that the patients with GS regimen had higher compliance, which may be related to the simplicity of treatment, lower adverse reactions and an intrinsic higher efficacy of S-1, so these patients could receive more cycles of treatment. The differences could not be observed may be owing to low numerosity.…”
Section: Discussionmentioning
confidence: 93%
“…Observation 3 G-based(246) Observation(238) 484 patients Julien Edeline, 2022 [ 28 ] NA EUROPEAN JOURNAL OF CANCER 2 Meta-analysis RCTs G-based vs. Observation 2 G-based(212) Observation(207) 419 patients Abdel-Rahman O, 2018 [ 29 ] 2017/06 COCHRANE DATABASE OF SYSTEMATIC REVIEWS 7 Meta-analysis RCTs G + S-1 vs. S-1 2 G + S-1(76) S-1(75) 151 patients Yan Li,2019 [ 30 ] 2018/10/06 FRONTIERS IN ONCOLOGY 25 Network Meta-analysis Restrospective; RCTs Folfox-4 vs. Observation NA Folfox-4(NA) Observation(NA) NA XP vs. GP NA XP(NA) GP(NA) NA G + S-1 vs. GC NA GS(NA) GC(NA) NA Jie Ying, 2019 [ 31 ] 2018/04 CRITICAL REVIEWS IN ONCOLOGY HEMATOLOGY 32 Network Meta-analysis Restrospective; RCTs G-based CHT vs. single CHT(mainly FU alone) …”
Section: Resultsmentioning
confidence: 99%